The Effect of Liquidity, Claim Expense Ratio, and Profitability on the Solvency of Life Insurance Companies in Indonesia - Bryan Carlo Iskandar; Fredella Colline (Universitas Negeri Surabaya, 2026)
Objective: This study examines the effect of liquidity (Current Ratio), claim burden (Claim Expense Ratio), and profitability (Return on Assets/ROA) on the solvency level of life insurance companies in Indonesia, proxied by Risk Based Capital (RBC). Using 159 firm-year observations from annual financial statements over the 2022–2024 period. Method: The study applies pooled multiple linear regression to panel-structured data. To address differences in measurement scales and improve coefficient comparability, the independent variables are standardized using Z-scores prior to estimation. The analysis incorporates classical diagnostic tests including normality, multicollinearity, heteroskedasticity, and autocorrelation as well as panel-data diagnostics to assess potential cross-sectional dependence and ensure the robustness of the estimates. Results: The results indicate that the model is jointly significant (F = 4.256; p = 0.006). Partially, Current Ratio has a positive and significant effect on RBC (B = 0.174; p = 0.028), while Claim Expense Ratio has a negative and significant effect (B = −0.246; p = 0.002). ROA does not significantly affect RBC (B = −0.036; p = 0.642). Novelty: The model explains 7.6% of the variation in RBC (R² = 0.076; Adjusted R² = 0.058), indicating that capital adequacy is influenced by broader structural and regulatory risk factors beyond short-term financial ratios. This implies that while liquidity and claims are critical, 92.4% of life insurance solvency is driven by other operational factors such as reinsurance or investment strategy.